A 19.0% efficiency achieved in CuOx-based inverted CH3NH3PbI3−xClx solar cells by an effective Cl doping method. (September 2016) - Rao, Haixia; Ye, Senyun; Sun, Weihai; Yan, Weibo; Li, Yunlong; Peng, Haitao; Liu, Zhiwei; Bian, Zuqiang; Li, Yongfang; Huang, Chunhui
Abstract: Hybrid organic-inorganic perovskite solar cells (PSCs) have exhibited huge potential for commercial application due to their various advantages such as high performance, flexible and so on. The inorganic hole conductor-based inverted planar PSCs are particularly significant on account of low cost and high stability. Here, we have successfully improved the power conversion efficiency (PCE) of this type of PSCs to 19.0% with CuOx as hole conductor and hybrid CH3 NH3 PbI3−x Clx perovskite as light absorber prepared by a novel Cl doping process based on a modified one-step fast deposition-crystallization method. This novel Cl doping process has proven to be a crucially effective procedure for enhancing the device performance due to the remarkable morphology and hole mobility improvement of the perovskite film, conspicuous intrinsic defects reduction in the film and prominent increase of the device recombination resistance. Graphical abstract: Highlights: A novel Cl doping process was first introduced in the PSCs. The Cl incorporation forms (MAPbI3 - x Clx and MAPbCl3 ) were studied. The Cl doping effect (morphology, carrier mobility and Rrec ) were investigated. A record PCE of 19.0% of the inorganic hole conductor-based PSCs was achieved.